ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PRODUK MULIA ULTIMATE DI PT PEGADAIAN CABANG TIMIKA - Revlin Lambang; Ahmad Tomu (Jurnal Ekonomi dan Bisnis, 2026)
The aim of this study is to analyse: (1) the effect of price on purchasing decisions, (2) the effect of ease of access on purchasing decisions, (3) the effect of promotions on purchasing decisions, and (4) the simultaneous effect of price, ease of access, and promotions on purchasing decisions. The data collection method used in this study was a questionnaire. Data analysis was conducted quantitatively using SPSS version 25. The results of this study are as follows: (1) Price has a positive and significant influence on purchasing decisions, indicating that consumers perceive the price to be reasonable and commensurate with product quality; (2) Ease of access also contributes significantly to purchasing decisions, reflecting that consumers find it easy to obtain information and make product purchases; (3) Promotion plays an important role in influencing purchasing decisions, indicating that attractive and clear promotional strategies can increase consumer interest in purchasing. (4) Simultaneously, price, ease of access, and promotion demonstrate that the combination of these three variables has a significant influence on purchasing decisions.